Do Butonese Women Need to Break the Cultural Taboos? (A Dilemma Among Butonese Women) - Mayaputri, Velmi; Nasa, Rikardus (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This research aims to analyze one of Indonesian ethnicity’s perspectives towards women empowerment and cultural taboos. In this context, the investigation focused on Butonese ethnic. Thus, this research employs ethnography research method. In attempt to gain the data, triangulations data collection techniques are employed including observation, FGD, and interview. The results reflected perceptions of Butonese Women from two different walk of life. In this case, the participants include housewives and career women. Butonese women proposed two different perspectives towards women empowerment. The first perspective is women empowerment considered as a radical resistance. Moreover, the second perspective claimed that women empowerment is an act of breaking the cultural taboos.